2022
DOI: 10.1155/2022/5372929
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic vs Nondynamic Assessments: Impacts on Intermediate EFL Learners’ Receptive Skills

Abstract: Listening and reading skills, which are two of the essential skills in the world of language learning, have established themselves in various academic fields. Many researchers have looked at teaching and developing these two receptive abilities, but less focus has been paid to assessing and testing them. Traditional evaluation has been used to examine learners for a long time, but new teaching methods should introduce new ways to test and assess students. This study attempted to investigate the impact of dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…TCLI is an appropriate method for language learning. Additionally, the results of this research study and those of Zhang and Hung (2012), Reed (2019), Abdulaal, Ramadan, Heji, andRobso (2022) are in agreement. They found that task-centered instruction used for students' motivation supports the beneficial effects of TCLI on grammar improvement.…”
Section: Discussionsupporting
confidence: 85%
“…TCLI is an appropriate method for language learning. Additionally, the results of this research study and those of Zhang and Hung (2012), Reed (2019), Abdulaal, Ramadan, Heji, andRobso (2022) are in agreement. They found that task-centered instruction used for students' motivation supports the beneficial effects of TCLI on grammar improvement.…”
Section: Discussionsupporting
confidence: 85%
“…e implication, as the size effect results showed, was that there was a strong correlation between CLA and writing skill development. is finding is backed by academics who have demonstrated that formulaic language plays a role in fostering writing abilities, particularly those whose research has been done in the context of the Saudi EFL [34]. Furthermore, research showing that L1 writing positively influences L2 writing [32] is quite consistent with the result that CLA improves EFL students' writing competence.…”
Section: Discussionsupporting
confidence: 53%
“…e bottom line is that those language learners who use this method have a greater chance of remembering and retrieving frequently used structures in their speech, and as they become more proficient, they choose L2 lexical chunks more automatically and rely less on their L1 counterparts, which are thought to scaffold the entire operation. EFL learners may find that they are unable to write well since they are unfamiliar with the appropriate lexical chunks that would ease their performance [34].…”
Section: Empirical Studiesmentioning
confidence: 99%
“…According to SCTF, learning doesn’t take place in a vacuum; it is impacted by meaningful social interactions in context. A youngster learns alongside an adult or a more experienced classmate, and language digesting takes place in the learner’s zone of proximal progress (Abdulaal et al, 2022b, Jafari, 2019; Jamali Kivi et al, 2022; J. Lantolf & Poehner, 2014; Teemant, 2018).…”
Section: Introductionmentioning
confidence: 99%